2006
DOI: 10.1007/s10532-005-1919-x
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Char Sorption over Substrate Concentration and Soil pH in Influencing Biodegradation of Benzonitrile

Abstract: Incomplete combustion of field crop residues results in the production of char, a material rich in charcoal-type substances. Consequently, char is an effective adsorbent of organic compounds and when incorporated into soil may adsorb soil-applied pesticides, thereby altering their susceptibility to biodegradation. We investigated the relative importance of char, soil pH and initial substrate concentration in biodegradation of pesticides in soils by measuring the biodegradation of benzonitrile in soil as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Similar results were found in a continuous-flow system, in which the fraction of applied PPCP biodegraded decreased dramatically when the starting concentration was changed from 0.1 g liter Ϫ1 to 100 g liter Ϫ1 (33). Initial substrate concentrations have been shown to influence the fraction of compound biodegraded for non-PPCP compounds as well, such as pesticide isopropyl N-phenylcarbamate (34), pesticide benzonitrile (35), and herbicide intermediate and biocide 2,4,5-trichlorophenol (36).…”
Section: Discussionsupporting
confidence: 67%
“…Similar results were found in a continuous-flow system, in which the fraction of applied PPCP biodegraded decreased dramatically when the starting concentration was changed from 0.1 g liter Ϫ1 to 100 g liter Ϫ1 (33). Initial substrate concentrations have been shown to influence the fraction of compound biodegraded for non-PPCP compounds as well, such as pesticide isopropyl N-phenylcarbamate (34), pesticide benzonitrile (35), and herbicide intermediate and biocide 2,4,5-trichlorophenol (36).…”
Section: Discussionsupporting
confidence: 67%
“…Biochar has been found to strongly adsorb herbicides and phytotoxic metals from the soil [32][33][34]. Similarly, a more developed body of research on crop residue char indicates that char is able to strongly adsorb herbicides and reduce their bioavailability better than other forms of organic matter [53,54].…”
Section: Immediate Phytotoxicity Of Biocharmentioning
confidence: 99%
“…The authors reported a 2.5-20 fold increase in the K f values following the char addition. Zhang et al (2006) studied the sorption of the pesticide benzonitrile in soil, wheat char and soil amended with the char at a rate of 1% (w/w) with the results of 40.5, >99, and 96.5% respectively, sorbed of the total of the pesticide initially applied. The wheat char was the dominant sorbent phase in the soil amended system, attributing approximately 90% of benzonitrile sorption to the wheat char and 10% to the soil.…”
Section: Effect Of Carbonaceous Materials On Pesticide Sorptionmentioning
confidence: 99%